Resource Mobilization and Financial Performance of Islamic Cooperative Societies in The South Western Nigeria - Azeez, Asif Olatubosun, (Ph.D.) (IJUS | International Journal of Umranic Studies, 2022)
Resource mobilization is an integral part of Islamic cooperative societies through its products such as, share, savings, development levies, sales of stationeries, reserve, investment fund, zakat, sadaqah, takaful, waqf, sukuk, etc. This paper hereby examined the resource mobilization strategy as regards to its impact on the financial development of the ICSs in the south western Nigeria. Descriptive research methodology was employed in the analysis of data obtained from the randomly selected ICSs through their financial statement and their ‘key informants’. Three major checks were carried out, this include; members share capital in relation to the total assets of the ICSs, growth in savings rate and loan management of the societies. The result indicated a positive asset management, growth in savings and good loan management, which jointly determined economic development of the societies in the studied area. It was therefore recommended that ICSs should explore more means of funds mobilization such as waqf, sukuk, proper financial record keeping and government regulation mechanism to enhance their socio-economic development roles.